Strategi Guru PAUD dalam Mengembangkan Kemampuan Fisik Motorik Anak Usia Dini Di Kotabumi Lampung Utara - Dewi Kurniawati (LP3M Pascasarjana STAI Ibnurusyd, 2026)
This study aims to analyze the strategies employed by Early Childhood Education (ECE) teachers in developing young children’s physical motor skills as part of holistic development. Motor skills, including both gross and fine motor abilities, are essential aspects that support children’s learning readiness as well as their cognitive, social, and emotional development. This research uses a qualitative approach with a descriptive study design. Data were collected through observations, interviews with teachers, and documentation of learning activities in ECE institutions. The findings reveal that teachers implement various strategies to develop children’s motor skills, including play-based learning, the use of educational media, outdoor activities, and the application of demonstration and hands-on practice methods. In addition, teachers adapt their strategies to the characteristics and developmental stages of the children. Supporting factors include the availability of facilities and teachers’ creativity, while the challenges involve limited resources and differences in children’s individual abilities. This study concludes that varied, creative, and child-centered strategies can effectively enhance children’s physical motor development. Therefore, improving teachers’ competencies and providing a supportive learning environment are crucial to optimize motor skill learning in early childhood education.